Hydroxyapatite/ZrO2@SiO2 bioceramic composite: Producing a promising biomaterial from natural sources - Padovini, David Santos Souza [UNESP]; de Azevedo-Silva, Lucas José; Ferrairo, Brunna Mota; Pereira, Letícia Florindo; Minim, Pedro Rodrigues; Pontes, Fenelon Martinho Lima [UNESP]; Fortulan, Carlos Alberto; Borges, Ana Flávia Sanches (Springer Nature, 2023)
ZrO2@SiO2 (core–shell) was prepared by mixing ZrO2 with SiO2 according to modified Stöber method. The nanostructures (15 wt%, ZrO2, SiO2, ZrO2@SiO2) were mixed with bovine hydroxyapatite (HA) and subjected to X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscope (FE-SEM), Vickers hardness (VH), and biaxial flexural strength (BFS). XRD showed no formation of secondary phases and FE-SEM revealed more homogeneous surface for ZrO2@SiO2. VH and BFS results showed statistically significant difference between all groups (p < 0.05). ZrO2@SiO2 significantly improved VH and BFS of HA. The ZrO2@SiO2 proved to be a promising material as a reinforcement for HA-based bioceramic. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Biomaterials; Core–shell; Hydroxyapatite; Nanoparticle